LRIG1 Extracellular Domain: Structure and Function Analysis. Issue 10 (22nd May 2015) - Xu, Yibin; Soo, Priscilla; Walker, Francesca; Zhang, Hui Hua; Redpath, Nicholas; Tan, Chin Wee; Nicola, Nicos A.; Adams, Timothy E.; Garrett, Thomas P.; Zhang, Jian-Guo; Burgess, Antony W.
Abstract: We have expressed and purified three soluble fragments of the human LRIG1-ECD ( e xtra c ellular d omain): the LRIG1-LRR ( l eucine- r ich r epeat) domain, the LRIG1-3Ig (immunoglobulin-like) domain, and the LRIG1-LRR-1Ig fragment using baculovirus vectors in insect cells. The two LRIG1 domains crystallised so that we have been able to determine the three-dimensional structures at 2.3 Å resolution. We developed a three-dimensional structure for the LRIG1-ECD using homology modelling based on the LINGO-1 structure. The LRIG1-LRR domain and the LRIG1-LRR-1Ig fragment are monomers in solution, whereas the LRIG1-3Ig domain appears to be dimeric. We could not detect any binding of the LRIG1 domains or the LRIG1-LRR-1Ig fragment to the EGF receptor (EGFR), either in solution using biosensor analysis or when the EGFR was expressed on the cell surface. The FLAG-tagged LRIG1-LRR-1Ig fragment binds weakly to colon cancer cells regardless of the presence of EGFRs. Similarly, neither the soluble LRIG1-LRR nor the LRIG1-3Ig domains nor the full-length LRIG1 co-expressed in HEK293 cells inhibited ligand-stimulated activation of cell-surface EGFR. Graphical abstract: Highlights: Three-dimensional structures have been determined for the LRR and Ig-like ectodomains of the LRIG1. Homology between LRIG1 and LINGO-1 led to a structural model of the LRIG1-ECD LRIG1-ECD binds to cells in the absence of the EGFR. No interaction between the LRIG1-ECD and several EGFR-ECD analogues was detected. Full-length LRIG1 expressed in HEK293 cells does not inhibit ligand activation of the EGFR.